Love's Wounds - Nazarian, Cynthia Nyree (Cornell University Press, 2017)
Love's Wounds takes an in-depth look at the widespread language of violence and abjection in early modern European love poetry. Beginning in fourteenth-century Italy, this book shows how Petrarch established a pattern of inequality between suffering poet and exalted Beloved rooted in political parrhēsia. Sixteenth- and early seventeenth-century French and English poets reshaped his model into an idiom of extravagant brutality coded to their own historical circumstances. Cynthia N. Nazarian argues that these poets exaggerated the posture of the downtrodden lover, adapting the rhetoric of powerless desire to forge a new
10.7591/9781501708268
Keywords: Liebesdichtung; Gewalt; Erniedrigung